Still Tools of Repression? Re-Assessing the Effect of Arms Imports on Physical Integrity Rights - Agnes Brender; Katharina Pfaff (University of Hamburg, Institute of Law and Economics (ILE), 2018)
Small arms and light weapons (SALWs) imports have been found to be linked to a worsening of human rights conditions in the importing state. In this paper, we reexamine the relationship of government's SALW imports and the decision to engage in violations of physical integrity rights using updated and more reliable repression data as well as proposing a different estimation strategy. Analyzing physical integrity rights violations and SALW imports of 176 countries from 1991 to 2010, empirical results indicate that SALW imports have a negative impact on respect for physical integrity rights. When disaggregating findings by regime type, we find that SALW imports in autocracies are associated with more repression, while we have mixed results for democracies.
Keywords: F14; H56; K33; 330; arms trade; SALW; repression